2017
DOI: 10.1017/s1751731117000404
|View full text |Cite
|
Sign up to set email alerts
|

Effect of egg storage duration and brooding temperatures on chick growth, intestine morphology and nutrient transporters

Abstract: The effects of egg storage duration (ESD) and brooding temperature (BT) on BW, intestine development and nutrient transporters of broiler chicks were investigated. A total of 396 chicks obtained from eggs stored at 18°C for 3 days (ESD3-18°C) or at 14°C for 14 days (ESD14-14°C) before incubation were exposed to three BTs. Temperatures were initially set at 32°C, 34°C and 30°C for control (BT-Cont), high (BT-High) and low (BT-Low) BTs, respectively. Brooding temperatures were decreased by 2°C each at days 2, 7,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The negative impact of prolonged storage duration on hatchability was reported by several authors [ 4 , 58 , 59 , 60 ]. It can be explained in part by morphological changes in the blastoderm [ 60 , 61 , 62 ] with increased cell apoptosis and necrosis [ 63 ] during storage.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The negative impact of prolonged storage duration on hatchability was reported by several authors [ 4 , 58 , 59 , 60 ]. It can be explained in part by morphological changes in the blastoderm [ 60 , 61 , 62 ] with increased cell apoptosis and necrosis [ 63 ] during storage.…”
Section: Discussionmentioning
confidence: 79%
“…These results agree with those of Reijrink et al [ 5 ], who noted that hatchlings after 4 days of storage were 0.1 cm longer and had 0.5 more grams of YFBM than hatchlings after 14 days of storage. Yalcin et al [ 58 ] also reported a decrease by −1.6 g of the hatchling weight when the storage duration was extended from 3 d to 14 d. Goliomytis et al [ 76 ] noted also, that 1-day-old chick BW and length were linearly negatively correlated with egg storage length. It can be suggested that due to the lower yolk sac utilization (also reflected in a lower yolk efficiency), less energy is available for the developing embryo and less energy can be deposited in organs, resulting in lower organ percentages.…”
Section: Discussionmentioning
confidence: 99%
“…(2004) noted also the absence of difference between intestine percentages with 7-day-old chickens from nonstored eggs, whereas Yalcin et al. (2016 , 2017) reported that a prolonged egg storage duration (14 vs. 3 D) negatively affected intestinal morphology. A larger villus width (+3.4 cm) and area (+6.5∗10 −2 μm 2 ) in the jejunum of hatchlings from eggs stored for 3 D was noted compared with eggs stored for 14 D ( Yalcin et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Long storage also affects the ability of the embryo to resume development once incubated, while embryos that survive long storage treatment undergo delayed hatching by several hours ( Christensen et al, 2002 ; Tona et al, 2003a ; Tona et al, 2003b ). Long storage of eggs can affect the intestinal morphology of the chicks, the expression of nutrient transporters ( Yalcin et al, 2016 ; Yalcin et al, 2017 ), chick immunocompetence ( Goliomytis et al, 2015 ) and hormonal metabolism ( Tona et al, 2003b ). Long storage may also have long-term negative effects on the quality and physiology of hatched chicks ( Tona et al, 2003a ; Tona et al, 2003b ; Reijrink et al, 2010 ; Yalcin et al, 2017 ; Mróz et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Long storage of eggs can affect the intestinal morphology of the chicks, the expression of nutrient transporters ( Yalcin et al, 2016 ; Yalcin et al, 2017 ), chick immunocompetence ( Goliomytis et al, 2015 ) and hormonal metabolism ( Tona et al, 2003b ). Long storage may also have long-term negative effects on the quality and physiology of hatched chicks ( Tona et al, 2003a ; Tona et al, 2003b ; Reijrink et al, 2010 ; Yalcin et al, 2017 ; Mróz et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%